X 500: More Than a Global Directory - Hong, James W.; Marshall, Andrew D.; Bauer, Michael A. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
The X.500 Directory was originally designed to act as an electronic replacement for paper telephone directories. It is the authors' belief that X.500 has a vital role to play in the emergence of information as a global commodity. In this paper, we explain how the X.500 Directory satisfies its original design goal of providing a global directory infrastructure